Implementasi Mindfulness sebagai Strategi Koping Stres pada Ibu Hamil: Studi Kasus Puskesmas Padangsari - Iis Kolama Sari; Nia Natalia; Dilla Maghdalena; Khairani Zikrinawati; Irma Masfia (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Pregnancy is a physically and mentally challenging phase for a woman. Changes in hormones, physical condition, and demands from the social environment can cause stress and anxiety. The purpose of this study was to investigate the use of mindfulness techniques as a way to cope with stress for pregnant women. This study used a qualitative methodology with a case study approach, involving three participants from a pregnant women's class held at Padangsari Community Health Center. Data were collected through observation, semi-structured interviews, and case study analysis, then the data were analyzed using thematic and narrative approaches. The findings of this study show that of the three participants, only one managed to apply mindfulness consistently, characterized by understanding and awareness of the changes she was experiencing, acceptance of the emotions that arose, and active engagement in the pregnancy experience. Meanwhile, the other two participants showed limitations in aspects of mindfulness, including self-observation, emotional disclosure, and social support, especially from their spouses. External factors such as the role of the husband as a support system and internal factors related to personality and daily routines influenced how effective the mindfulness application was. This study concludes that the application of mindfulness can help pregnant women manage stress and improve their emotional health, but also requires support from the environment and regular practice.